PERBANDINGAN METODE DOUBLE MOVING AVERAGE DAN DOUBLE EXPONENTIAL SMOOTHING (BROWN) TERHADAP TINGKAT PENGANGGURAN TERBUKA DI KOTA PADANG PANJANG - Fishuri, Nufhika; Ikhsan, Easbi; Fitri, Fadhilah; Permana, Dony (LPPM Universitas Bina Bangsa, 2025)
Unemployment occurs because of a mismatch between the demand for jobs and job seekers' qualifications. Many job vacancies require diploma or degree graduates, so unemployment is one of the problems faced by Padang Panjang City. To overcome TPT in Padang Panjang City, one of them needs to do forecasting to see how the TPT rate will occur in the coming year. This research uses a forecasting method by comparing the Double Moving Average (DMA) and Double Exponential Smoothing (DES) forecasting values of the unemployment rate in Padang Panjang City from 2006 to 2023. This forecasting is done to provide insight into the condition of the workforce in Padang Panjang City in the future. The forecasting results show that in 2024, there will be an increase of 0.42%, and for the next 2 years, there will be a decrease.